2021
DOI: 10.1038/s41588-021-00962-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning enables genetic analysis of the human thoracic aorta

Abstract: Enlargement or aneurysm of the aorta predisposes to dissection, an important cause of sudden death. We trained a deep learning model to evaluate the dimensions of the ascending and descending thoracic aorta in 4.6 million cardiac magnetic resonance images from the UK Biobank. We then conducted genome-wide association studies in 39,688 individuals, identifying 82 loci associated with ascending and 47 with descending thoracic aortic diameter, of which 14 loci overlapped. Transcriptome-wide analyses, rare-variant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
147
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 82 publications
2
147
0
1
Order By: Relevance
“…In addition, summary data from GWAS of ascending aortic (AA) and descending aortic (DA) diameters were obtained. AA and DA diameters were evaluated in cardiac magnetic resonance images from the UK Biobank by a deep learning model ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, summary data from GWAS of ascending aortic (AA) and descending aortic (DA) diameters were obtained. AA and DA diameters were evaluated in cardiac magnetic resonance images from the UK Biobank by a deep learning model ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…Of note, FBN1 was present both in our GWAS gene set and the HTAAD gene set. We then tested whether the 21 putative causal TAAD risk genes were enriched in speci c cell types identi ed from publicly available single nuclear RNA expression data (snRNA) from ascending and descending thoracic aorta 33 . Using the fast gene set enrichment software, we observed that the causal TAAD gene set was signi cantly enriched in VSMC (P = 0.0078), and a suggestive enrichment was also observed with broblasts (P = 0.02), though this was no longer signi cant after Bonferroni correction (P < 0.01 = 0.05/5 cell types; Supplementary Table 17).…”
Section: Gene Expression Analyses Reveal Taad-relevant Cell Typesmentioning
confidence: 99%
“…Finally, we sought to identify relevant cell types for the individual putative causal TAAD risk genes leveraging scRNA sequencing data from normal and aneurysmal ascending aortic aneurysm tissue 34 and snRNA sequencing data from normal ascending and descending thoracic aorta 33 . For the 9 genes we hypothesized promote TAAD risk through changes in aortic gene expression ("candidate causal genes through changes in expression" in Supplementary Table 14), we rst qualitatively assessed for a prioritized cell type through: 1) the percentage of cells expressing the gene in a given cell type cluster, and 2) the magnitude of average gene expression in each cell type (Figure 4a,b,c).…”
Section: Gene Expression Analyses Reveal Taad-relevant Cell Typesmentioning
confidence: 99%
See 2 more Smart Citations